Comparative Analysis of Hematological Profiles in Diabetic Mice Treated with D-Allulose and Neoagaro-Oligosaccharides - Salsabila Faradisa Nuris; Wiwin Ariesti; Tri Rini Nuringtyas; Budi Saksono; Rahadian Yudo Hartantyo; Fajar Sofyantoro; Nastiti Wijayanti (Quagga: Jurnal Pendidikan dan Biologi, 2026)
Diabetes mellitus is characterized by chronic hyperglycemia that induces oxidative stress and inflammation, contributing to hematological dysfunction and increased systemic risk. This study comparatively evaluated the effects of D-allulose and neoagarooligosaccharides (NAOS) on hematological parameters in BALB/c mice with type 2 diabetes induced by streptozotocin. Experimental groups consisted of control, negative control, positive control (metformin), and treatment groups receiving D-allulose (0.05, 0.1, 0.2 g/kg BW) or NAOS (100, 200, 400 mg/kg BW) orally for 28 days. Hematological assessments included red blood cell (RBC) count, erythrocyte indices (hemoglobin, hematocrit, mean corpuscular hemoglobin), leukocyte count, and lymphocyte levels. Negative controls displayed decreased RBC parameters and lymphocytes, with elevated leukocytes, indicating hematological impairment associated with hyperglycemia. D-allulose improved RBC count, hemoglobin, and MCH, while reducing leukocyte count and elevating lymphocytes, especially at lower doses. NAOS primarily enhanced erythrocyte quality by improving hemoglobin, hematocrit, and MCH, while also modulating leukocyte and lymphocyte profiles. Overall, D-allulose was more effective in restoring erythrocyte quantity, whereas NAOS contributed more prominently to erythrocyte index improvement. Both agents show potential in reducing hematological disorders associated with inflammation in diabetes cases.